Shirley Temple : Darling Double Feature - Little Miss Marker and Now and Forever - 1894-1968; Lawrence, Vincent; 1890-1946; Thalberg, Sylvia; Lighton, Louis D.; (Louis Duryea); 1895-1963; Hathaway, Henry; 1898-1985; Kirkland, Jack; 1902-1969.; Hall, Alexander; et al. (Universal City, CA, 2016)
Little Miss Marker: The adorable child actor single- handedly melts the hearts of a gang of hardened gangsters when shes left as an IOU or marker for a debt. Now and Forever: The irresistible child actor stars with screen legends Gary Cooper and Carole Lombard in this endearing tale of love, honor and sacrifice that will steal your heart away; now and forever.
Keywords: Kirkland, Jack; 1902-1969; Film adaptations; Gangsters; Drama; Debt; Drama; Fathers and daughters; Drama; Video recordings for the hearing impaired; Film adaptations; Feature films